Product Expansion dari Endowment Factor Pepaya Desa Mayangan Kecamatan Gumukmas Kabupaten Jember - Lilis Yuliati; Siti Komariah; Moh. Adenan (IAI Darussalam, 2020)
The activity service aims to increase the productivity of the